Italy and the history of preventive conservation - Simon Lambert (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Italy is a point of reference for the conservation community worldwide, but it has yet to make a definitive leap towards preventive conservation. This paper examines some of the reasons to explain this, in the hope that this may be useful for other countries. After a brief look at the history of preventive conservation from Antiquity to the Second World War, two seldom-discussed Italian initiatives are presented: The Franceschini Commission (1964) and the Pilot plan for the programmed conservation of cultural heritage in Umbria (1976).